Gastrointestinal System Involvement in Pediatric Patients with Acute SARS-CoV-2 Infection - Ozlem KALAYCIK SENGUL; Burcin BEKEN; Zehra OZTURK; Seyma OZPINAR; Gizem OZKAN; Gizem GUNGOR (Medeniyet Medical Journal)
Objective: The prevalence of gastrointestinal symptoms in coronavirus disease-2019 (COVID-19) has been reported widely. In this study, the prevalence of gastrointestinal system (GIS) involvement in pediatric COVID-19 and its effect on prognosis were investigated. Methods: Children (aged 0-18 years) with acute COVID-19 were included in the study. The patients were grouped according to system involvement: isolated respiratory system (RS), isolated GIS, and combination of both (RS+GIS). These groups were compared in terms of demographic data, clinical characteristics, laboratory and imaging findings, and hospitalization. Results: A total of 223 pediatric patients were included in the study. Of these patients, 19 were asymptomatic, 12 were diagnosed with a multisystem inflammatory syndrome in children, 21 had chronic disorders that may affect disease severity, and 27 had symptoms not related to RS or GIS. The remaining 144 patients were classified according to system involvement: 79 (35.4%), 14 (6.3%), and 51 (22.9%) had isolated RS, isolated GIS, and RS+GIS involvement, respectively. The GIS group was much younger than the RS group (median, 30 and 150 months, respectively, p=0.006). Three patients from the RS group were followed in the intensive care unit (ICU). Moreover, 17 (21.5%) and 4 (7.8%) patients from the RS group had severe-critical respiratory symptoms, in the RS+GIS group had severe-critical respiratory symptoms (p=0.039). Conclusions: Our study showed that GIS involvement in children with COVID-19 is more prevalent than RS involvement in the younger age group. Respiratory symptom severity and ICU admission also decreased with accompanying GIS involvement. GIS involvement